Risk factors and outcomes in 385 cases of ulnar nerve submuscular transposition. (May 2021) - Davis, Gavin A.; Lal, Trisha; Hearps, Stephen J.C.
Highlights: Patients were included in this study with risk factors commonly excluded in other series. Application of published exclusion criteria would have resulted in exclusion of ½–⅔ of our cohort. Symptomatic improvement reported in 91.05% patients. Improved results were observed in younger patients and those without peripheral neuropathy. There were no deep infections. Abstract: Submuscular transposition (SMT) for treatment of ulnar nerve entrapment is commonly performed, however published comparisons of surgical techniques exclude a high proportion of the at-risk population encountered in real world practice. To examine the influence of risk factors on the clinical outcome following SMT we performed a retrospective review of all patients who underwent SMT, including patient self-reported outcome and Louisiana State University Medical Centre ulnar nerve grading scale. A total of 403 ulnar nerves were operated, with follow-up data available for 385 cases (359 patients). Risk factors (including smoking, diabetes, previous elbow trauma/pathology, subluxation, workers' compensation) were reported in 266 of 385 surgeries (69.09%). SMT was the primary procedure in 339 nerves (88.05%), revision procedure in 46 nerves (11.95%). At last follow up 91.05% reported symptomatic improvement. Nerve grade improvement in 71.09% of primary and 67.39% revision surgery (p = 0.605). No significant difference in improvement was identified between demographic and risk categories, except for patient reported improvement in those without peripheral neuropathy (90.59% vs 73.33%, p = 0.027), and those not improved were on average older than those improved (62.94 vs. 55.68 years, p = 0.012). Superficial infection occurred in 2.6% and there were no deep infections. Application of published exclusion criteria would have resulted in exclusion of ½–⅔ of our cohort. SMT in patients with a history of elbow trauma, diabetes, workers compensation, smoking history, nerve subluxation or revision surgery have similar outcomes compared to those without these factors, whilst improved results were observed in younger patients and those without peripheral neuropathy.